Adjustable Resonance Frequency of RF-MEMS Capacitor by Using Comb- Drive Actuators: A Design Approaches - Tamsir, Agus Santoso; Wijaya, Sandy Tannu; Majlis, Dato’ Burhanuddin Yeop (Makara Journal of Technology, 2014)
The needs of smaller size RF varactor is a must today, and MEMS comes to be the potential one. In this paper we proposed an adjustable resonance RF-MEMS varactor by using comb-drive actuators placing in each side of the square movable plate. In our preliminary simulation, we found that the device can work properly but some constraints comes such as the dominancies of harmonic resonance frequencies that influences into the nominal capacitances. Therefore for the next step of development we have to find out the window of the structural dimension for a certain spans and a certain operating frequencies.